2016
DOI: 10.1186/s12981-016-0121-z
|View full text |Cite
|
Sign up to set email alerts
|

Cases of antiretroviral-associated gynaecomastia reported to the National HIV & Tuberculosis Health Care Worker Hotline in South Africa

Abstract: BackgroundGynaecomastia is associated with exposure to antiretroviral therapy (ART), in particular efavirenz. There is limited data on clinical characteristics of patients with ART-associated gynaecomastia in resource-limited settings and little guidance on the optimal management of this adverse drug reaction (ADR). We describe the clinical characteristics, management and outcomes of gynaecomastia cases reported to the National HIV & Tuberculosis Health Care Worker Hotline in South Africa.MethodsWe identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…Resolution of gynaecomastia is generally slow, taking months and may be incomplete in a small percentage. 67 It is, therefore, important to manage the expectations of the patient in this regard.…”
Section: Antiretroviral Therapy Toxicity Monitoring and Managementmentioning
confidence: 99%
“…Resolution of gynaecomastia is generally slow, taking months and may be incomplete in a small percentage. 67 It is, therefore, important to manage the expectations of the patient in this regard.…”
Section: Antiretroviral Therapy Toxicity Monitoring and Managementmentioning
confidence: 99%
“…2,3 In contrast, hypogonadism among HIV-infected adult men seems to be a condition that has been underestimated in frequency, and it was an independent factor associated with gynaecomazia. 8 In the reported case, patient was exposed to numerous risk factors like drugs, HCV infection and hypogonadism. He took anti-tubercular drugs twelve years before the onset of symptoms and taking Efavirenz based ART for seven years before he noticed breast swelling, which differs from most of the studies.…”
Section: Discussionmentioning
confidence: 98%
“…Two other hypothesized mechanisms have been suggested for ART-associated gynaecomazia are: a) immune restoration may increase breast tissue oestrogen availability, and b) efavirenz has been shown to increase the area under the curve of ethinyl oestradiol by at least 37%, thereby elevating the oestrogen-androgen ratio. 7,8 Opportunistic infection, lymphoma, Kaposi's sarcoma and pseudoangiomatous stromal hyperplasia (PASH) form part of the further differential diagnosis. 6 It was also found that gynaecomazia among HIV-infected patients is related to hypogonadism, rather than to an adverse effect of antiretroviral drugs, while other study report that lipoatrophy and chronic hepatitis C are independent factors associated with gynaecomazia.…”
Section: Discussionmentioning
confidence: 99%
“…11 Two other hypothesized mechanisms have been suggested for ART-associated gynecomastia: immune restoration may increase breast tissue oestrogen availability, and efavirenz has been shown to increase the area under the curve of ethinyloestradiol by at least 37%, thereby elevating the oestrogen-androgen ratio. 12 The introduction of highly active antiretroviral therapy (HAART) in developed countries in the late 90s has been associated with a remarkable decrease in AIDS-related mortality. This decrease in mortality has changed the perspective of HIV infection from that of a rapidly fatal to a chronic manageable infection.…”
Section: Discussionmentioning
confidence: 99%